Assessment of Student Engagement with Team-Based Learning in Nursing - Lynn, Adwoa; Holbach, Jessica (My University, 2014)
The purpose of this study was to assess student engagement in a sample of undergraduate nursing students before and after participating in a nursing course using the Team-Based Learning strategy.
Color poster with text, images, and graphs.
Keywords: Team-based nursing (TBL); Nursing education; Classroom Survey of Student Engagement; CLASSE student; Posters